Auxiliar de residencia de obra en procesos constructivos para el proyecto multifamiliar torres del norte en la ciudad de Sogamoso. (2022)
The company GM Construcciones Asociados S.A.S is located in the city of Sogamoso Boyacá, this company has extensive experience in the construction of housing infrastructure of both social interest type VIS and No VIS. It is currently executing the Torres del Norte multifamily project, which consists of 3 towers and will be executed in 3 stages. The first tower has 8 floors, the second with 10 floors, and the last one in which the 12-story practice was carried out, is called a tower. 1 (Stage 3) which is made up of two parking floors with 26 private parking spaces and 3 commercial premises on these two floors, in turn has 11 apartment floors with 7 residential units per floor for a total of 77 apartments, this tower It has a total built area of 8,353.08 m². To support the construction phase, the company requires civil engineering interns who fulfill the role of construction resident assistant. This document reflects the work that was carried out as an intern during the execution of his practice in support of the resident engineer from the sixth mezzanine plate to the tenth plate in the Torres del Norte multifamily project, providing support in the monitoring and control tasks. of the construction stage.